Let's get this party haunted! - Stine, R. L. (New York : Delacorte Press, 2005)
Max's twelfth birthday party turns into a major disaster when ghosts Nicky and Tara boycott it, and sinister events spin out of control.
"A Parachute Press book."
Keywords: Ghosts; Birthdays; Parties; Horror stories